Notational analysis of female´s singles badminton matches in relation at stress area - Peralvarez, E.; Torres-Luque, G.; Cabello-Manrique, D.; Rivas, F.; Femia, P.; Urena, A. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
The aim of this study was to determine the gestural structure of female´s singles badminton matches in relation at stress area. 36 single´s badminton matches in Olympic Games were selected. Matches were played with the current "rally point scoring" system, where the one who wins the best of 3 games of 21 points is the winner. Official videos recorded by the organizations of the Beijing 2008 Olympic Games were used to carry out the analysis of the matches. Matches were analyzed with Kinovea 8.15 software and analysis of all games was done following the methods of Anguera (2003). 28 types of strokes were selected (Fesba, 2008). Three-stress zone were selected (Fesba, 2008): stress zone; moderate stress; zone without stress. The results showed a total of 17225 strokes analyzed. The results shown that predominant stroke that generated stress zone: forehand low stroke net drop (22.7%); Backhand low stroke net drop (22.4%) and Forehand overhead stroke Drop (19.3%). Strokes that generated moderate stress were: Forehand low stroke Net Drop (12.1%); Backhand low stroke (13.4%) and; Forehand overhead stroke Clear (13.8%) and Drop (13.3%). Strokes that generated zone without stress was: Forehand low stroke Lob (13.4%); Backhand low stroke Lob (14.1%); Forehand overhead stroke Clear (15.8%) and Smash (18.2%). These studies are necessary for the technical and tactical planning and specific training in female´s singles badminton matches.